"The Good, the Bad and the Ugly": Interplay of Innate Immunity and Inflammation. (10th August 2022) - Alemán, Mercedes
Abstract : Innate immunity recognizes microorganisms through certain invariant receptors named pattern recognition receptors (PRRs) by sensing conserved pathogen-associated molecular patterns (PAMPs). Their recognition activates several signaling pathways that lead the transcription of inflammatory mediators, contributing to trigger a very rapid inflammatory cascade aiming to contain the local infection as well as activating and instructing the adaptive immunity in a specific and synchronized immune response according to the microorganism. Inflammation is a coordinated process involving the secretion of cytokines and chemokines by macrophages and neutrophils leading to the migration of other leukocytes along the endothelium into the injured tissue. Sustained inflammatory responses can cause deleterious effects by promoting the development of autoimmune disorders, allergies, cancer, and other immune pathologies, while weak signals could exacerbate the severity of the disease. Therefore, PRR-mediated signal transduction must be tightly regulated to maintain host immune homeostasis. Innate immunity deficiencies and strategies deployed by microbes to avoid inflammatory responses lead to an altered immune response that allows the pathogen to proliferate causing death or uncontrolled inflammation. This review analyzes the complexity of the immune response at the beginning of the disease focusing on COVID-19 disease and the importance of unraveling its mechanisms to be considered when treating diseases and designing vaccines.